Fifty-year habitat subdivision enhances soil microbial biomass and diversity across subtropical land-bridge islands - Wu, Ying; Wang, Bing; Wu, Liji; Liu, Shengen; Yue, Lingyan; Wu, Jianping; Chen, Dima (Frontiers in Microbiology, 2022)
Although habitat loss and subdivision are considered main causes of sharp declines in biodiversity, there is still great uncertainty concerning the response of soil microbial biomass, diversity, and assemblage to habitat subdivision at the regional scale. Here, we selected 61 subtropical land-bridge islands (with small, medium, and large land areas) with a 50-year history of habitat subdivision and 9 adjacent mainland sites to investigate how habitat subdivision-induced unequal-sized patches and isolation affects biomass, diversity, and assemblages of soil bacteria and fungi. We found that the soil bacterial and fungal biomass on all unequal-sized islands were higher than that on mainland, while soil bacterial and fungal richness on the medium-sized islands were higher than that on mainland and other-sized islands. The habitat subdivision-induced increases in microbial biomass or richness were mainly associated with the changes in subdivision-specified habitat heterogeneities, especial for soil pH and soil moisture. Habitat subdivision reduced soil bacterial dissimilarity on medium-sized islands but did not affect soil fungal dissimilarity on islands of any size. The habitat fragment-induced changes in soil microbial dissimilarity were mainly associated with microbial richness. In summary, our results based on the responses of soil microbial communities from subtropical land-bridge islands are not consistent with the island biogeographical hypotheses but are to some extent consistent with the tradeoff between competition and dispersal. These findings indicate that the response of soil microbial communities to habitat subdivision differed by degree of subdivision and strongly related to habitat heterogeneity, and the distribution of microbial diversity among islands is also affected by tradeoff between competition and dispersal.